2016
DOI: 10.1136/jech-2016-207887
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between employment histories and frailty trajectories in later life: evidence from the English Longitudinal Study of Ageing

Abstract: BackgroundGiven the acceleration of population ageing and policy changes to extend working lives, evidence is needed on the ability of older adults to work for longer. To understand more about the health impacts of work, this study examined the relationship between employment histories before retirement and trajectories of frailty thereafter.MethodsThe sample comprised 2765 women and 1621 men from the English Longitudinal Study of Ageing. We used gendered typologies of life-time employment and a frailty index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Over the past years, an increasing number of longitudinal studies have evaluated trajectories of health deficits accumulation (DA) in older adults and their main determinants [3][4][5][6][7][8][9]. Most of these studies have relied on the frailty index, a multidimensional index defined as the proportion of health deficits present in an individual out of the total number of deficits considered, which has shown to be a good predictor of adverse outcomes (i.e., falls, hospitalization, disability, institutionalization and death) in older adults [10].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, an increasing number of longitudinal studies have evaluated trajectories of health deficits accumulation (DA) in older adults and their main determinants [3][4][5][6][7][8][9]. Most of these studies have relied on the frailty index, a multidimensional index defined as the proportion of health deficits present in an individual out of the total number of deficits considered, which has shown to be a good predictor of adverse outcomes (i.e., falls, hospitalization, disability, institutionalization and death) in older adults [10].…”
Section: Introductionmentioning
confidence: 99%
“…self-rated health, mortality or frailty), the methods used to identify and summarize lifecourse patterns, and the country considered (USA or England), these studies have reached varying conclusions on whether work–family histories predict differences in later life health. 10 , 13 , 17 Lu et al . , 17 examining frailty trajectories among English women aged 60+, reported beneficial effects for those who took a short career break before returning to work part-time compared with women who worked mostly full-time throughout (FTT).…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 13 , 17 Lu et al . , 17 examining frailty trajectories among English women aged 60+, reported beneficial effects for those who took a short career break before returning to work part-time compared with women who worked mostly full-time throughout (FTT). In American mothers aged 55+, Sabbath et al 13 found lower mortality in those who returned to work after briefly staying home with children compared with non-workers, always workers and those who delayed work re-entry.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, for health and health-related outcomes, occupational epidemiology has assessed exposure-outcome association measures, whether simple or accumulated, at one point in time. Few studies have involved longitudinal analyses of the effect of prior working life on health [11][12][13][14][15][16]. From the standpoint of occupational epidemiology, because a person lives in a multidimensional and multilevel context, an approach from a lifecourse perspective could elucidate relevant events in a person's working life that manifest and shape health status over time [17].…”
Section: Introductionmentioning
confidence: 99%